2021
DOI: 10.3390/en14113069
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the Infrastructure of Systems Used in Smart Cities for the Planning of Transport and Communication Systems in Cities

Abstract: Modern mobility and adaptation of transport and communication systems to the requirements of the inhabitants are both inseparable elements of the developed concept of smart cities. One of the important stages in the implementation of this concept is the planning stage, taking into account the complexity and a large number of determinants that impact the effectiveness of decisions related to the planning of transport, communication and logistic systems. The purpose of the article is to lay out a model of a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…De Falco et al underline the fact that as far as the notion of a smart city is concerned it embraces "toolkit of technological solutions and policy interventions aimed at implementing urban technologies to monitor urban systems and improve their efficacy through real-time monitoring and big data analytics" (De Falco et al, 2019). It can be confirmed that "smart cities are an example of how the use of IoT will help make objects smart via a combination of devices, sensors, electronic tags and advanced communication networks" (Stępniak et al 2021). Y.…”
Section: The Characteristic Of a Smart Citymentioning
confidence: 99%
“…De Falco et al underline the fact that as far as the notion of a smart city is concerned it embraces "toolkit of technological solutions and policy interventions aimed at implementing urban technologies to monitor urban systems and improve their efficacy through real-time monitoring and big data analytics" (De Falco et al, 2019). It can be confirmed that "smart cities are an example of how the use of IoT will help make objects smart via a combination of devices, sensors, electronic tags and advanced communication networks" (Stępniak et al 2021). Y.…”
Section: The Characteristic Of a Smart Citymentioning
confidence: 99%
“…The overarching goal is to create urban environments that not only harness technological advancements for operational efficiency but also prioritise the well-being of residents by promoting sustainability, connectivity, and overall livability. The synergy between technology and urban planning thus becomes a key driver in shaping cities that are not only smart but also resilient, inclusive, and conducive to the flourishing of vibrant communities (Gracias et al, 2023;Hui et al, 2023;Stępniak et al, 2021).…”
Section: Addressing the Question Of Health Technology And Built Envir...mentioning
confidence: 99%
“…Songdo has also introduced a self-driving bus service that uses autonomous vehicles to transport passengers around the city. The city's ITS system is used to manage traffic, parking, and energy consumption (Richter et al, 2020;Stępniak et al, 2021).…”
Section: Its Integration In Songdo South Koreamentioning
confidence: 99%